An Analysis Of Learning Materials Needs Of Japanese Language At Nursing School In Tomohon City - Kapoh, R J (Journal of Educational Method and Technology, 2019)
This study aims to produce an overview of the needs of Japanese teaching materials at the Tomohon "Bethesda" Nursing Academy. The approach and method used is a mixed approach or a mixed method that is a research approach that combines qualitative and quantitative forms. Creswell, (2014: 5) Data obtained by observation, survey and interview techniques. By using a mixed method approach, the data collected in the form of text are described qualitatively. Likewise with data through a questionnaire, tabulated in percentage and subsequently described qualitatively. The results of the needs analysis show that both learners and instructors, all of them need teaching materials that the contents of the material in a variety of skills should be in accordance with the special field of expertise that is the field of nursing that is well-graded, and well designed too. Furthermore, in the learning process it should also be equipped with cassettes, videos, and sufficient practice questions and good evaluation. This study recommends that teaching materials be developed that reflect comprehensive needs in the area of health expertise, especially nursing.Â Keywords: Needs Analysis, Japanese Language Teaching Materials, School of Nursing.